Advancing the development of national childhood cancer-care strategies in Latin America - McMaster Health Forum (McMaster Health Forum. Video interviews: Advancing the development of national childhood cancer-care strategies in Latin America. Geneva, Switzerland: McMaster Health Forum, 8 June 2015., 2015)
Video interviews with participants in a stakeholder dialogue about advancing the development of childhood cancer-care strategies in Latin America (on YouTube).
https://www.youtube.com/playlist?list=PL3eLSKVraEeD9EnCk90CnBTf9LiKUQVPf
Keywords: national; childhood; cancer; Latin America